Analysis of Number of Layers and Volume Fraction of Fiber Against Shock Load and Composite Compressive Strength Wind Turbine Propeller - Kris Witono; Pondi Udianto; Heru Prasetyo; Sugeng Hadi Susilo (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
The manufacture of wind turbine blades has a very high risk of failure, especially in the manufacturing section or in this case the material structure. If the structure of the propeller material is not able to withstand the very high pressure and air flow, it will result in the failure of the material structure when it is in use. For this reason, the purpose of this study was to determine the composition of composite materials that have high strength and toughness properties and are suitable for wind turbine propellers. The method used in this research is experimental. The independent variables include the number of layers and the volume fraction of straw fiber. The dependent variables are shock load and compressive strength. Each compression test specimen is made with a gauge length of 100mm, a width of 25mm, and a thickness of 2.5mm. While the impact test specimens are made equal to l25mm long, l2mm wide, l2mm high, and 2mm notch. The results showed that the bending strength of the straw fiber composite with 6 layers had an increasing trend as the number of layers increased. The highest bending strength with the number of piles of 6 layers and the lowest strength with the number of piles of 2 layers. In addition, the volume fraction is very influential on the bending stress of the straw composite matrix. It can be seen that the matrix with a volume fraction of 50% has the greatest bending stress in each number of layers, both 2, 4 and 6. For the impact test, it is found that the optimal number of layers occurs in the number of 2 layers with a volume fraction of 33%. The shock load tends to decrease. Meanwhile, based on the volume fraction, the larger the volume fraction, the smaller the shock load that can be received by the straw fiber composite material.